HUBUNGAN EDUKASI FARMASIS TERHADAP PENINGKATAN KUALITAS HIDUP PASIEN ASMA - Sunarti Sunarti (Jurnal Farmasi Indonesia, 2015)
Asthma is a respiratory disease an dis often found to be a problem in the community and require the selection and use of appropriate medications to reducethe frequency of asthma attacks.The provision of appropriate education and useful by pharmacists is expected to improv equality of life better. The purpose of this study wast on determine the effect of pharmacist education on the qualityof life of patients with asthma,as well as to determine the correlation quality of life of asthma patients in the out patient Center for Public Health Pulmonary Surakarta. Research methods using experimental design with a control group design with pretest post test. Patients who received therapy for asthma were divided into two groups,treatment group and control group. Data was collected by conducting interviews and quality of life using the SGRQ questionnaire (St.George's Respiratory Questionnaire). Analysis of statistical tests showed that the quality of life was used paired t test analysis and t independent test results p = -0.000 (Î± <0.05), whereas the mean score of quality of life, p = 0.000 (Î± <0.05) there are differences meaningful before and after education between the control group and the treatment group. This study concludes that education can affect the quality of life of patients in the education group compared to the control group.